The relationship of corporate social responsibilities initiatives and consumer loyalty - Nor Maizatul Asma, Misman (2015)
The trend towards social responsibility in recent years has amplified the interest of consumers in their consumption as well as purchase behaviour. Given the growing importance of social responsibility in the retail industry, in Malaysia, it remains imperative for the retail industry to understand the social responsibility as the determinants of customers’ loyalty. Therefore, this study aims to underline the relationship of customer centric, green environment, and philanthropic towards customer loyalty. This study are quantitative in nature by using the sample of 172 respondents. Data analysis was performed using SPSS system. From the analysis, it found that all of CSR initiatives have positive significant effect on customer loyalty. As a result, philanthropic has the greatest effect on retail industry while customer centric the least influencing factor on loyalty.